1991
DOI: 10.1677/jme.0.0060137
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by progesterone of the high-affinity state of myometrial β-adrenergic receptor and of adenylate cyclase activity in the pregnant rat

Abstract: The effects of pregnancy or progesterone dominance on the beta-adrenergic responsiveness of the uterus were studied in myometrial membranes from mid- and late-pregnant rats (day 15 and on the 16th h of day 22 of pregnancy respectively) or 24 h after administration of progesterone. Levels of the high (RH)- and low (RL)-affinity states of the beta-adrenergic receptor were determined by competition experiments between 125I-labelled cyanopindolol binding and the selective beta-agonist isoproterenol. The ratio KL/K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
2
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 18 publications
5
26
2
1
Order By: Relevance
“…Activation of rat -ARs, which are selectively localized in this muscle layer , significantly decreases myometrial InsP production through both cAMP-dependent and -independent mechanisms (Khac et al 1996, Dodge et al 1999, Mhaouty-Kodja et al 2004. At the end of pregnancy, progesterone withdrawal and the subsequent -AR desensitization (Cohen-Tannoudji et al 1991) probably relieve the PLC system from inhibitory constraints in the longitudinal muscle. Concomitantly, the increase in oestradiol concentrations enhances transcription of the transduction entities involved in the PLC signalling pathway (OTR, PLC 1 and PLC 3) in the circular muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of rat -ARs, which are selectively localized in this muscle layer , significantly decreases myometrial InsP production through both cAMP-dependent and -independent mechanisms (Khac et al 1996, Dodge et al 1999, Mhaouty-Kodja et al 2004. At the end of pregnancy, progesterone withdrawal and the subsequent -AR desensitization (Cohen-Tannoudji et al 1991) probably relieve the PLC system from inhibitory constraints in the longitudinal muscle. Concomitantly, the increase in oestradiol concentrations enhances transcription of the transduction entities involved in the PLC signalling pathway (OTR, PLC 1 and PLC 3) in the circular muscle.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, this subtype is selectively up-regulated by progesterone at the level of gene transcription (Vivat et al 1992). In addition, progesterone has been shown to stabilize the high affinity state of the receptor, thus increasing the coupling of the 2 -ARs to adenylyl cyclase (Cohen-Tannoudji et al 1991) and facilitating uterine quiescence. In contrast, the 1 -ARs play an important role in the mechanism of parturition, as supported by several lines of evidence (Legrand & Maltier 1986, Pennefather et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Potentiation of cAMP production by the 2 /G i pathway at midpregnancy is related to the -AR activation of G s , high levels of G i3 and G i2 proteins and the presence of type II and IV adenylyl cyclases in the rat myometrium . At the end of pregnancy, the stimulabilities of the cAMP generating system by isoproterenol (Litime et al 1989, Cohen-Tannoudji et al 1991) and 2 agonists decline. Concomitantly, a reduction in the myometrial levels of ADP-ribosylated G s and G i3 as well as in the 2A -AR subtype expression is observed (Elwardy-Mérézak et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…The number of b-ARs also dropped during the last 7 h before term in rats, which may contribute to the weakening effect of b-AR agonists (Maltier & Legrand 1988). Cohen-Tannoudji et al (1991) demonstrated a pregnancy-dependent uncoupling of b-ARs and a decreased responsiveness of rat myometrial adenyl cyclase to isoproterenol. These changes were pronounced in the last few hours before delivery in the rat and controlled by progesterone.…”
Section: Introductionmentioning
confidence: 96%